Ectopic pregnancy is associated with increased risk of displaced implantation window: a retrospective study - Hong Zeng; Yahan Chang; Nenghui Liu; Shuyi Li (BMC Pregnancy and Childbirth)
Abstract Background To evaluate the risk factors associated with WOI (window of implantation) displacement based on ERT (endometrial receptivity test), and to confirm the association of ectopic pregnancy with WOI displacement. Methods This is a retrospective study at the Reproductive Medicine Center of Xiangya Hospital from January 2020 to April 2024, consisting of 934 patients who performed ERT. The patients underwent 3771 assisted reproductive technology (ART) cycles and 2629 embryo transfer (ET) cycles, with each patient experiencing at least one implantation failure. The study utilized generalized estimation equation (GEE) models to examine factors associated with WOI displacement, adjusting for confounding factors like age, body mass index (BMI), and infertility type. Non-linear relationships between age or BMI with WOI displacement were explored using generalized additive models (GAM) with thresholds detected by segmented regression. Results Among the patients, 60.17% were in the receptive phase, 39.40% in the pre-receptive phase, and 0.43% in the post-receptive phase. Ectopic pregnancy history increased the risk of WOI displacement by 62% (aOR 1.62, 95%CI 1.03–2.53, P = 0.035), patients over 35 years old had a 50% higher risk of WOI displacement compared to patients under 34 (aOR 1.50, 95% CI 1.12-2.00, P = 0.007). Secondary infertility showed a 26% lower risk of WOI displacement than primary infertility without statistical significance (aOR 0.74 95% CI 0.54–1.02, P = 0.062). BMI ≥ 22 kg/m2 was associated with a 25% increased risk of WOI displacement without statistical significance (aOR 1.25, 95% CI 0.94–1.67, P = 0.12). Conclusion Ectopic pregnancy and advanced age (≥ 35) are significantly associated with increased risk of WOI displacement. Primary infertility and higher BMI (≥ 22 kg/m2) tend to increase the risk of WOI displacement though without statistical significance. Clinical trial number Not applicable.